2018
DOI: 10.1371/journal.pone.0193746
|View full text |Cite|
|
Sign up to set email alerts
|

Inter-vendor reproducibility of left and right ventricular cardiovascular magnetic resonance myocardial feature-tracking

Abstract: AimSince cardiovascular magnetic resonance feature-tracking (CMR-FT) has been demonstrated to be of incremental clinical merit we investigated the interchangeability of global left and right ventricular strain parameters between different CMR-FT software solutions.Material and methodsCMR-cine images of 10 patients without significant reduction in LVEF and RVEF and 10 patients with a significantly impaired systolic function were analyzed using two different types of FT-software (TomTec, Germany; QStrain, Nether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 38 publications
5
50
1
7
Order By: Relevance
“…Prior studies have investigated the impact of repeated measures on reproducibility of FT-CMR [ 43 , 44 ] where the differences in intra- and inter-observer variability were assessed based on single and averaged measurements (two and three repetitions with subsequent averaging of results, respectively). It was found that averaging of the results of repeated analyses improves the reproducibility of LA strain measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have investigated the impact of repeated measures on reproducibility of FT-CMR [ 43 , 44 ] where the differences in intra- and inter-observer variability were assessed based on single and averaged measurements (two and three repetitions with subsequent averaging of results, respectively). It was found that averaging of the results of repeated analyses improves the reproducibility of LA strain measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inter-vendor comparisons have been performed in prior studies [ 43 , 44 , 46 ] to determine differences in strain measurements between commercially available FT-CMR software packages (TomTec, Medis QStrain and Circle Cardiovascular Imaging). The inter-vendor agreement was reasonably good for LV global circumferential strain and longitudinal strain, but was lower in right ventricular global longitudinal and radial strains [ 44 , 46 ]. The time for post-processing of a given case did not vary between the different types of software [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Introduced in 2009, CMR feature tracking (FT) 12 is a postprocessing solution that is applied on routinely acquired balanced steady-state free precession (bSSFP) cine images with high blood-tissue contrast. Although CMR FT has been validated extensively, [13][14][15][16][17] significant concerns regarding intervendor agreement remain, leading to slow clinical implementation. 18 Furthermore, agreement with the reference standard for CMR-derived deformation assessment CMR tagging has been inconclusive, 19,20 with considerable dependence on observer experience.…”
Section: Introductionmentioning
confidence: 99%
“…Final strain values were calculated from the average of three repetitions. 16,17 The CMR tagging was performed on identical LV and short-axis slices using a triggered 2D TAG sequence generating an orthogonal saturation grid (grid spacing of 7 mm, tag grid angle of 45°). Typical parameters were as follows: FOV = 340 × 340 mm 2 , slice thickness = 8 mm, voxel size = 1.9 × 1.9 × 8 mm 3 , reconstructed solution = 1.2 × 1.2 × 8 mm 3 , flip angle = 15°, TE = 1.8 ms, and TR = 4.2 ms. Endocardial and epicardial borders were manually traced in end systole, which were then automatically propagated using a commercially available software (Segment version 2.2 R6960) for tagged image analyses ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the coefficient of variation of 3D GRS was not good (Figure 4). GRS represented strain throughout the entire myocardial wall from subepicardium to subendocardium and was consequently much more affected by through plane motion and complex diastolic and systolic twisting motion [29].…”
Section: Discussionmentioning
confidence: 99%